Single-Cell Level Response of HIV-Specific and Cytomegalovirus-Specific CD4 T Cells Correlate With Viral Control in Chronic HIV-1 Subtype A Infection - Eller, Michael A.; Eller, Leigh Anne; Ratto-Kim, Silvia; Ouma, Benson J.; Lo, Vicky; Souza, Mark de; Guwatudde, David; Nails, Barbara; Michael, Nelson L.; Wabwire-Mangen, Fred; Robb, Merlin L.; Marovich, Mary A.; et al. (JAIDS Journal of Acquired Immune Deficiency Syndromes, 2012)
HIV-1 subtype A is the second most prevalent subtype globally and is associated with reduced viral load, higher CD4 absolute counts, and slower disease progression. To study the possible role of T cells associated with better outcome, we examined CD4 and CD8 T-cell responses against HIV-1 and cytomegalovirus (CMV) in Ugandans infected with subtype A HIV-1. Methods: T-cell responses were investigated using flow cytometry and novel subtype A variant inclusive peptide (VIP) sets designed for this evaluation. CD4 T-cell responses focused primarily on Gag, whereas CD8 T-cell responses were broadly directed against Gag, gp41, and Nef VIP sets. CD4 T cells primarily responded with interferon (IFN)-g, whereas CD8 cells were more diverse with degranulation (CD107a), IFN-g, and macrophage inflammatory protein (MIP)-1b production. Results: No relationship was observed between CD8 T-cell responses and the HIV-1 load. Similarly, the frequency of CD4 T cells responding to these antigens did not associate with viral control. However, in CD4 T cells responding against Gag or CMV, the IFN-g intensity, indicative of the production at the singlecell level, was inversely proportional to viral load. No significant relationship was found between T-cell effector/memory phenotype and viral control. Conclusions: The per cell production of IFN-g in CD4 T cells responding to HIV-1 or CMV correlated with viral control in chronic HIV-1 subtype A infection. These data suggest that quantitative aspects at the single-cell level may be more important than the frequency of antigen-specific CD4 T cells in HIV-1 subtype A infection control.
Keywords: T cells; HIV-1; AIDS; Viral infections; Memory